(untitled) (Eurasian Medical Research Periodical, 2023)
The article provides modern data on the problem of etiology, pathogenesis, clinical picture and treatment of generalized periodontitis. The authors came to the conclusion that treatment should be comprehensive and aimed at eliminating inflammation in the periodontal area, eliminating the periodontal pocket, stimulating reparative osteogenesis, restoring function, and preventing negative effects on the general health and quality of life of patients. The use of conductors in drugs for the treatment of inflammatory and destructive periodontal diseases is due to their ability to increase the transmucous conductivity of drugs to the inflammation focus, allowing you to create an effective concentration of the active drug component that is part of the composition in the entire volume of periodontal lesions and maintain it throughout the entire period of treatment.